EVALUASI KINERJA MENGAJAR GURU KELAS V BERSERTIFIKASI DI DAERAH BINAAN 2 KECAMATAN PARAKAN - Setyowati, Tambah; Sulasmono, Bambang Suteng (Universitas Kristen Satya Wacana, 2015)
This research has three main objectives : (1) to evaluate the teachers in planningÂ the lesson; (2) to evaluate the teachers in class; (2) to evaluate the teachers in gradingÂ the studyâs result. This research conducted in Target areas 2 Districts Parakan in secondÂ semester of 2014/2015 which subject is the certified teachers in nine elementary schoolsÂ in Parakan. This research is an evaluated research based on mix method. The data wasÂ gained by observation, interview, document, and survey. The result showed that 88.89%Â certified teachers in Parakan had a good record in teaching and 11.11% were in aÂ very good phase even in the planning, teaching, or the evaluating. Though there areÂ some aspect that need to be fixed such as : (1) planning the chosen studyâs medium andÂ source (2) implementing the ICT (3) conducting contextual lesson; (3) the selection ofmethod; and (4) the questions to evaluate the study.